PENGARUH BIAYA PRODUKSI DAN JUMLAH PENJUALAN TERHADAP KEUNTUNGAN DI CV DEVINA LIVING DENPASAR - I Wayan Astawa; I Gede Bayu Kurniawan (Majalah Ilmiah Widyacakra, 2020)
ABSTRACTThe tittle research is Influence of Production Cost and Total Sales to Profit at CV. Devina LivingDenpasar. Costs arising from the acquisition or processing of a product or service will affect theselling price of the product concerned. The selling price of the product or service will affect theamount of sales of the product or service in question. The ability of companies in determining theright cost of production will affect the rate of profit earned, the greater the amount of salesobtained the greater the profits. The purpose of this study is to determine the effect of productioncosts and the amount of sales on profits in the CV. Devina Living Denpasar. Sources of dataused are primary and secondary data. Data in analysis by using computer program SPSS forWindows ver 22. Methods of data collection in this study using interviewing techniques anddocumentation studies, by recording documents - documents owned CV. Devina Living. Dataanalysis technique using multiple regression analysis. The results obtained from the statisticalanalysis showed that the magnitude of the effect of production costs and the amount of sales onprofits in the CV. Devina Living is 88.5%, by testing the hypothesis using t-test, with the resultthat variable of production cost (X1) have significant effect with t-result equal to -3,077 and sig0,005 to variable of profit (Y) and variable of sales amount (X2 ) had significant effect with tresult of 5,284 and sig 0,000 toward profit variable (Y).